Implementasi Kebijakan Parkir Berlangganan dalam Menunjang Pendapatan Asli Daerah (PAD) Kabupaten Sidoarjo - Balahmar, Ahmad Riyadh U (JKMP (Jurnal Kebijakan dan Manajemen Publik), 2013)
The purposes of this research were to know and describe subscription service in Sidoarjo Regency and implementation of the policy of the subscription in supporting local revenue. Today’s main issue which is appears on public service is the low quality of public services rendered by government officials. One interesting issue to study is the parking subscription service in Sidoarjo Regency. In this case, researcher studied about the parking subscription policy, as imposed by the government, whether it has already supported the local revenue or not. This was a descriptive qualitative research, which used approach in a qualitative manner. The research result indicated that the policy of the parking subscription has been able to support local revenue but the implementation needs to be improvinsied.